2020
DOI: 10.1177/2325967120966310
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Play and Competitive Outcomes After Ulnar Collateral Ligament Reconstruction Among Baseball Players: A Systematic Review

Abstract: Background: Ulnar collateral ligament (UCL) reconstruction (UCLR) is very common in baseball. However, no review has compared the return-to-play (RTP) and in-game performance statistics of pitchers after primary and revision UCLR as well as of position players after UCLR. Purpose: To review, synthesize, and evaluate the published literature on outcomes after UCLR in baseball players to determine RTP and competitive outcomes among various populations of baseball players. Study Design: Systematic review; Level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“… 7 Previously established factors affecting RTP include surgical technique, graft fixation technique, level of competition, and sport and position played. 4 , 20 , 21 With the dramatic increase in the number of UCL reconstruction procedures performed annually and the expansion of UCL reconstruction candidates to include younger patient populations, 7 , 9 , 10 it is imperative to more thoroughly understand factors affecting RTP after UCL reconstruction.…”
mentioning
confidence: 99%
“… 7 Previously established factors affecting RTP include surgical technique, graft fixation technique, level of competition, and sport and position played. 4 , 20 , 21 With the dramatic increase in the number of UCL reconstruction procedures performed annually and the expansion of UCL reconstruction candidates to include younger patient populations, 7 , 9 , 10 it is imperative to more thoroughly understand factors affecting RTP after UCL reconstruction.…”
mentioning
confidence: 99%
“…Rationale: Controversies remain whether or not the patients undergoing ligament reconstruction surgery for elbow instability [146][147][148] should be routinely administered VTE prophylaxis.…”
Section: Antoon Van Raebroeckx Surena Namdarimentioning
confidence: 99%
“…Erickson et al 18 reported on 20 studies with an 86.2% pooled RTS rate. Thomas et al 50 reported that among baseball players, return-to-play rates after UCL reconstruction varied by position. They found that catchers return to play less frequently than pitchers, infielders, or outfielders, and that pitching workloads decrease after UCL reconstruction.…”
mentioning
confidence: 99%
“…They found that catchers return to play less frequently than pitchers, infielders, or outfielders, and that pitching workloads decrease after UCL reconstruction. 50 However, to the best of our knowledge, no previous systematic review has characterized the reasons for why athletes fail to RTS after UCL reconstruction.…”
mentioning
confidence: 99%